All-in-one cushion - Join, Tiara; Roslan, Nurul Natasha Adila; M Said, Salasiah (Universiti Teknologi MARA, Kedah, 2017)
Information agency serves different types of users. Each of users has their own preference while searching for the information. There is a need for libraries, to cater the user’s need to make sure they are feeling comfortable while in a library. All-in-One Cushion is one of innovative product in an information agency. It became a hub for those who needs a leisure place for reading, resting and having an idea while thinking. The problem arise in a library commonly regarding to the save space for the chair, shelves and many more. Other than that, user easy to feel bored with the same decoration in a library. In future, this cushion capable to fulfill the library needs. The novelty and uniqueness of this All-in-One Cushion is users don’t have to go to the shelf or magazine rack to read it. Users also can use the power outlet which is embedded in this cushion. Users also can put their stationaries while reading and doing their homework.